ANALYZING THE INFLUENCE OF ONLINE LEARNING TOWARD LEARNING MOTIVATION DURING POST COVID-19 PANDEMIC - Della Anggun Sari; Rina Rabtul Janah; Amelda Syaputri; Sri Wahyuni (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2022)
Currently, learning at school is conducted online or offline. When the implementation of offline learning has been ruled, numerous things have changed, especially for students. This cannot be separated from the habits of students and teachers, who have been involved in the distance learning system for over two years, where students used to follow online learning. This study aims to analyze the influence of offline education on learning motivation post-Covid-19 pandemic. This method in this article is library research which compiles the information through books, notes, magazines, and others. The result shows several changes in student learning motivation post-covid-19 pandemic. Students more easily understand materials they have studied rather than learning conducted online, and students also do productive activities. They seem to be more independent. In addition, other changes are seen in that students comfortably participate in online classes rather than offline classes, which the offline participation less than online participation. This is a chance of student motivation post-covid-19 pandemic.